2006
DOI: 10.1007/s00114-005-0080-z
|View full text |Cite
|
Sign up to set email alerts
|

Are dioxin-like contaminants responsible for the eel (Anguilla anguilla) drama?

Abstract: Eel populations worldwide are dangerously close to collapsing. Our study is the first to show that current levels of dioxin-like contaminants are strong candidates because of their devastating effects on development and survival of eel embryos. Female and male silver eels were artificially stimulated to maturation and reproduction by treatment with carp pituitary extracts and hCG, respectively. During maturation of female European silver eels, about 60 g fat per kg eel is incorporated in the oocytes. Together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
119
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 18 publications
4
119
0
1
Order By: Relevance
“…Apart from increasing the number of migrant eels, it is important to address potential spawner quality issues. Recent studies have indicated that infection with the parasitic swim bladder nematode Anguillicola crassus (Palstra et al, 2007) and EVEX eel rhabdovirus (van Ginneken et al, 2005), and contamination with dioxin-like PCBs (Palstra et al, 2006) and with cadmium (Pierron et al, 2008) could be responsible for migration or reproduction impairment. It is therefore essential to combine research on escapement with studies of migrant eel quality.…”
Section: Tableau IIImentioning
confidence: 99%
“…Apart from increasing the number of migrant eels, it is important to address potential spawner quality issues. Recent studies have indicated that infection with the parasitic swim bladder nematode Anguillicola crassus (Palstra et al, 2007) and EVEX eel rhabdovirus (van Ginneken et al, 2005), and contamination with dioxin-like PCBs (Palstra et al, 2006) and with cadmium (Pierron et al, 2008) could be responsible for migration or reproduction impairment. It is therefore essential to combine research on escapement with studies of migrant eel quality.…”
Section: Tableau IIImentioning
confidence: 99%
“…Such radical changes in the eel population have been attributed, inter alia, to excessive exploitation of the species, deterioration of the environment, climatic changes and infestation of the swimming bladder with the Anguillicoloides crassus nematode (e.g., Friedland et al 2007;Belpaire et al 2009;Clevestam et al 2011). Intensive research to develop an artificial reproduction technique for this species (Palstra et al 2005), as well as stocking actions aimed at increasing its population in the waters of Europe (Vogel 2010) is among the measures taken to save the European eel from total extinction.…”
Section: Introductionmentioning
confidence: 99%
“…Contamination (e.g. by PCBs) might impair fertility (Palstra et al 2006) and affect lipid metabolism resulting in insufficient energy reserves to power successful migration and reproduction (Belpaire et al 2009). The Council of the European Union established a framework and measures for the recovery and sustainable use of the stock of European eel (European Commission 2007) and requires the preparation and implementation of national Eel Management Plans.…”
Section: Introductionmentioning
confidence: 99%